Upwind or downwind: the spring arrival of Arctic Terns Sterna paradisaea at Troms, north Norway. Issue 1 (1st June 2016) - Barrett, Robert T.
ABSTRACT: Arctic Terns Sterna paradisaea have a record long migration between their breeding grounds in the Arctic and wintering areas in the Antarctic. Nevertheless, return dates to north Norway were remarkably constant over a 35-year period (1981–2015), with Arctic Terns arriving in Troms within a 13-day time window in mid to late May. Since 1993, arrival dates have advanced by about four days. No relationships were found between arrival dates and large-scale weather proxies such as the North Atlantic Oscillation or sea temperatures, but when terns were approaching Troms, headwinds tended to delay arrivals whereas tailwinds advanced them.